ANALISA STABILISASI FISIK TANAH PADA PEKERJAAN JALAN GAMPONG ALUE DUA KOTA LANGSA - Harry Luciano, Aldi; Novita Lydia, Ellida; Sari, Firda (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2024)
Soil characteristics depend on soil texture, density, environmental conditions and other factors. The use of selected embankment materials aims to increase the stability of the subgrade in the supporting layer (Capping Layer). The aim of this research is to determine the physical characteristics of the selected embankment soil, determine the soil density value in the laboratory and determine the soil density value in the field. The methods used to determine the physical properties of soil are water content testing, specific weight testing, Atterberg limit testing, sieve analysis testing, soil compaction in the laboratory is carried out using the standard proctor testing method, soil density testing in the field is carried out using the sandcone test method. The results of the soil compaction test in the standard proctor laboratory obtained a max ?d value of 1.397 grams/cm3 and an optimum W of 19.49%. In the Sandcone Test, the values for the degree of field density were obtained, namely STA 0+000 of 115%, STA 0+050 of 106%, STA 0+100 of 103%. The results of testing the physical properties of selected embankment soil include field water content of 16.70%, specific weight (Gs) of 2.66, plasticity index (PI) of 2.13% and sieve analysis that passed number 200 was 10.93%. Based on the AASHTO classification system, it can be concluded that the selected embankment land used in Mulia Indah Hamlet, Alue Dua Village, Langsa Baro District, is included in group A-2-4.